Avaliação dos preparos da superfície cerâmica para a colagem de acessórios ortodônticos - Savoldi, Jean Erick; Salazar, Marcio [UNESP]; Sábio, Sérgio; Cuoghi, Osmar Aparecido; Terada, Helio Hissashi [UNESP] (My University, 2011)
The purpose of this study was to evaluate the effects of two conditioning methods used to enhance the shear strength of orthodontic brackets bonded to porcelain surfaces. A total of 18 feldspathic specimens were used. The specimens were divided randomly into two groups (n = 9): group free silane, the porcelain specimens were etched with hidrofuoric acid 10% (Acid Gel-Maquira) for 4 minutes followed by adhesive-primer (Transbond XT) and the metallic brackets (Morelli Roth Light .022" x .030") were bonded with a light-cured microfilled resin (Transbond XT Light Cure Orthodontic Adhesive); group silane, the porcelain specimens were etched with hidrofuoric acid 10% (Acid Gel-Maquira) for 4 minutes followed by silane (Silano Ângelus) for 1 minute, adhesive-primer (Transbond XT) and the metallic brackets (Morelli Roth Light .022" x .030") were bonded with a light-cured microfilled resin (Transbond XT Light Cure Orthodontic Adhesive). All specimens were stored in solution of artificial saliva at ambient temperature for 24 hours. The debonding was done with shear strength through a universal testing machine (DL 500-Emic) calibrated with a fixed speed of 1mm/minute. Statical analysis was performed using the Student t test. The results indicated that in the free silane group the mean bond strength was 9,97 MPA, significantly lower than the silane group, that was 12,38 MPa (p < 0,05). The both groups were effective for bonding, although the silane group had the highest bond strength values.

O objetivo deste trabalho foi avaliar os efeitos de dois métodos de preparo utilizados para aumentar a força de adesão de bráquetes colados em superfícies cerâmicas. Um total de 18 corpos de prova foi usado, sendo divididos aleatoriamente em dois grupos (n = 9): grupo sem silano, os corpos de prova foram condicionados com ácido hidrofluorídrico 10% (Ácido Gel-Maquira) por quatro minutos, seguido da aplicação de adesivo (Transbond XT) e os bráquetes (Morelli Roth Light .022" x .030") foram colados com resina fotopolimerizável (Transbond XT Light Cure Orthodontic Adhesive); grupo com silano, os corpos de prova foram condicionados com ácido hidrofluorídrico 10% (Ácido Gel-Maquira) por quatro minutos, seguido da aplicação do silano (Silano Ângelus), da aplicação de adesivo (Transbond XT) e os bráquetes (Morelli Roth Light .022" x .030") foram colados com resina fotopolimerizável (Transbond XT Light Cure Orthodontic Adhesive). Todos os corpos de prova foram armazenados em solução de saliva artificial por 24 horas em temperatura ambiente. O teste de tração foi realizado por uma máquina de ensaio universal (DL 500-Emic) calibrada com velocidade fixa de 1 mm/minuto. Foi usado o teste t Student para análise estatística. Os resultados indicaram que a força média de adesão do grupo sem silano foi de 9,97 MPa, significantemente menor do que a força média do grupo com silano, que foi de 12,38 MPa (p < 0,05). Os dois grupos foram eficientes para colagem, embora o grupo com silano tenha tido o valor de adesão maior.
Evaluation of ceramic surface preparation for bonding orthodontic accessories
Keywords: Tensile strength; Ceramic; Orthodontic brackets; Resistência à tração; Cerâmica; Bráquetes ortodônticos